1997
DOI: 10.1161/01.atv.17.4.797
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Secretion of von Willebrand Factor and Fibronectin in Megakaryocytes at Different Phases of Maturation

Abstract: Our goals have been to define the biochemical characteristics of megakaryocytes during maturation that are critical for platelet assembly and release into the circulation and to introduce biochemical markers for megakaryocytes. To achieve these goals, we have studied fibronectin (FN) and von Willebrand factor (vWF), which are large adhesive proteins that are synthesized by megakaryocytes, stored in alpha granules, and thought to have a fundamental role in hemostasis. The study demonstrated that vWF is primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…Previous studies done by Schick et al . have demonstrated that VWF is primarily synthesized in mature pig megakaryocytes, 7.5 times more than in immature megakaryocytes; 14.5% and 4.6% of total synthesized VWF was secreted into culture media by mature and immature pig megakaryocytes, respectively. In their tissue culture system, approximately 13% of synthesized VWF was secreted into culture media from megakaryocytes (both mature and immature).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies done by Schick et al . have demonstrated that VWF is primarily synthesized in mature pig megakaryocytes, 7.5 times more than in immature megakaryocytes; 14.5% and 4.6% of total synthesized VWF was secreted into culture media by mature and immature pig megakaryocytes, respectively. In their tissue culture system, approximately 13% of synthesized VWF was secreted into culture media from megakaryocytes (both mature and immature).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, examination of the role of Pyk2 as an integration point for integrin-mediated signaling in OBs revealed that the MK-mediated increase in Pyk2 levels in OBs was unaltered by treatment of cultures with integrin-blocker RGDS at doses we have previously shown to be efficacious for reducing MK-mediated OB proliferation (Figure 3). 17 This finding was unexpected since Pyk2 is known to be activated by phosphorylation downstream of integrin engagement in other cell types, including OCs, 34 MKs express and secrete fibronectin, 41–43 a β 1 -binding integrin ligand, and titration of RGDS into MK-OB cultures resulted in a significant reduction in OB proliferation. 17 It should be noted that our findings do not, however, exclude the possibility that integrin activation in response to MKs, results in an increase in the phosphorylation and therefore catalytic activity of Pyk2 in OBs.…”
Section: Discussionmentioning
confidence: 99%
“…17 RNA from CD34 ϩ cells was used only for quantitative real-time polymerase chain reaction (qPCR) analysis of PLAU transcription, as the quantities harvested precluded other analyses. RNA from day-7 and -13 megakaryocytes and platelets was used for qPCR analysis of PLAU, VWF (control for increased mRNA during megakaryocyte differentiation 18 ), and VCL 7 transcription. RNA from platelets was also used to evaluate CAMK2G transcription in QPD.…”
Section: Analyses Of Mrna By Quantitative Reverse-transcription Polymmentioning
confidence: 99%